2016
DOI: 10.1177/0269215515606198
|View full text |Cite
|
Sign up to set email alerts
|

Ottawa Panel evidence-based clinical practice guidelines for therapeutic exercise in the management of hip osteoarthritis

Abstract: The Ottawa Panel recommends land-based therapeutic exercise, notably strength training, for management of hip osteoarthritis in reducing pain, stiffness and self-reported disability, and improving physical function and range of motion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 25 publications
3
57
0
1
Order By: Relevance
“…Previous studies emphasised the positive effect of knowledge and insight on the ability of an individual to manage a progressive disorder and to function in one's daily life (Selman et al, 2009;De Rezende, 2017). Information and knowledge has the capacity to reduce your pain, improve compliance with exercise and most importantly, it could improve your health-seeking behaviour (Brosseau et al, 2010;Mann and Gooberman-Hill, 2011;Cobbing et al, 2014). Similarly to this study, a report from Uganda found that at times the only source of information for a patient was a magazine article or a family member/friend, which could lead to misconceptions and the circulation of myths (Selman et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies emphasised the positive effect of knowledge and insight on the ability of an individual to manage a progressive disorder and to function in one's daily life (Selman et al, 2009;De Rezende, 2017). Information and knowledge has the capacity to reduce your pain, improve compliance with exercise and most importantly, it could improve your health-seeking behaviour (Brosseau et al, 2010;Mann and Gooberman-Hill, 2011;Cobbing et al, 2014). Similarly to this study, a report from Uganda found that at times the only source of information for a patient was a magazine article or a family member/friend, which could lead to misconceptions and the circulation of myths (Selman et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Two of the biggest limitations to the efficacy of exercise-based treatment are prescription and patient adherence. Poor exercise prescription for people with knee osteoarthritis can result in either overloading the affected joint, leading to increases in pain and swelling; or more commonly, prescribed exercises that are not challenging enough to facilitate a training effect (Brosseau et al, 2016;Fransen et al, 2015;Hunter, 2017). The inclusion of strategies to improve the adherence to the prescribed exercises could boost treatment effectiveness O'Brien, Bassett, & McNair, 2013).…”
Section: Myth 5: Conservative Treatments Are Ineffectual and Only Desmentioning
confidence: 99%
“…Physiotherapists should only consider referring a person for orthopaedic review (TJR) after the patient has failed an appropriate exercise programme that meets best practice clinical guidelines (Brosseau et al, 2016;Fransen et al, 2015).…”
Section: Practice Point Mythmentioning
confidence: 99%
“…It has been used by researchers to translate scientific knowledge and professional experience into informed judgment, in order to support effective decision-making [29]. The Delphi technique has been reported to be the most widely used consensus method for developing clinical guidelines [30][31][32]. Delphi techniques have been used to develop guidelines, to establish consensus on the use of the guidelines and to establish and evaluate how well a clinical practice is conforming to guidelines [33].…”
Section: Rationale For the Use Of The Delphi Technique In This Projectmentioning
confidence: 99%